Uji Modifikasi Lemari Pengering Pati Talas Kimpul (Xanthosoma sagittifolium) sebagai Eksipien dalam Formulasi Tablet Terhadap Lama Pengeringan - Shan Amadeus; I Gusti Ngurah Agung Dewantara Putra (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The physical properties of excipients are very important to know for the manufacture of good tablets. Starch or amylum is an additional material that is often used in the manufacture of tablets. The physical properties of starch or powder that are good for tablets can give the desired effect if they have good quality. Unmodified starch does not have good compressibility and has great friability, and capping will occur in the tablet. Taro taro as a potential starch can be used as an excipient in the manufacture of tablets because it has a high starch content. Taro taro used as an excipient needs to be modified physically and chemically to produce derivatives that have better and more specific pharmaceutical characteristics, especially for the manufacture of tablets. The purpose of this study was to determine whether the physical properties of taro starch matched the parameters of good physical properties. Tests carried out included organoleptic tests which obtained powder like flour, had no odor, had no taste and had a white color, Knowledge test obtained dark blue in modified taro starch solution after being given iodine, Microscopic tests obtained taro starch results which had the arrangement is clustered with the hilus located in the middle, the shape of the hilus is in the form of a point, a straight line. The water content test obtained the water content value of each modified starch based on the length of drying time using a drying cabinet of 9.40% for drying for 24 hours, 8.42 % for drying for 48 hours, and 7.9% for drying for 72 hours and pH Test Produces a pH value of 6.52 for drying for 24 hours, 6.22 for drying for 48 hours and 5.92 for drying for 72 hours.